Minus Peran Pemerintah Daerah dalam Pemenuhan Hak Penyandang Disabilitas Di Kabupaten Bone - P, Wildana; Fahri, Marjana; Amir, Nursakinah (IAIN Bone, 2022)
Guarantee of rights is not only given to citizens who have physical and mental perfection but also to vulnerable groups such as persons with disabilities. Persons with disabilities have equal rights and opportunities and must be protected and fulfilled. Efforts to fulfill the rights of persons with disabilities in Bone district as in item 1) Inclusive Education; 2) Sports Development; 3) Legal Protection; 4) Care Program for Persons with Disabilities.Obstacles to the Association of People with Disabilities of Indonesia (PPDI) Bone Regency in Fulfilling the Rights of Persons with Disabilities Based on Regional Regulation of Bone Regency Number 5 of 2017 concerning Protection and Fulfillment of Rights of People with Disabilities are 1) People with Disabilities; 2) Families of Persons with Disabilities; 3) Budget Constraints; 4) Government.